Manipulating Perovskite Precursor Solidification toward 21% Pristine MAPbI3 Solar Cells. Issue 5 (1st April 2021) - Guo, Yuanhang; Wu, Haotian; Liu, Zhixin; Shan, Shiqi; Niu, Benfang; Lian, Xiaomei; Zuo, Lijian; Chen, Hongzheng
Abstract : Controlling the crystallization of perovskite film is critical for high‐performance perovskite solar cells (PVSCs), and temperature is the key factor dominating the nucleation and crystal growth. Herein, it is demonstrated that the inconspicuous ambient temperature plays an important role in reaching high‐quality perovskite film and high‐performance PVSCs. It is observed that the ambient temperature greatly affects the composition of as‐prepared perovskite film, which dramatically influences the perovskite film morphology during the subsequent annealing process. Remarkably, the device prepared at the optimal ambient temperature of 29 °C exhibits the best power conversion efficiency of 20.91% with little hysteresis. This represents one of the best results for inverted PVSCs based on pristine MAPbI3 system. In addition, the PVSC prepared at 29 °C shows good stability with 80% of its initial efficiency after 30d in air with a humidity of 45%. Overall, the importance of ambient temperature for crystallization of the perovskite film is emphasized, and this work should have implications for controlling the morphology for high‐performance PVSCs. Abstract : It is discovered that the morphology of the as‐prepared perovskite film is greatly affected by the surrounding temperature during spin‐coating. The optimal surrounding temperature of 29 °C is observed to dramatically enlarge the perovskite crystal size and increase the power conversion efficiency of perovskite solar cell to 20.91%, which is the highest reported value among inverted MAPbI3 solar cells.